2016
DOI: 10.3171/2015.12.peds14645
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation for recurrent tethered cord syndrome in a pediatric patient: case report

Abstract: The authors present a patient with a lipomyelomeningocele and worsening back pain due to recurrent tethered cord syndrome. Because of the increased risk and unlikely improvement in symptoms with repeated surgical untethering, she was offered an alternative treatment with a trial of dorsal spinal cord stimulation. She had an excellent response to the percutaneous trial, and a permanent implant was placed, with good initial results. The authors review her case as well as the treatment options, indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…68 Our systematic review did reveal a patient treated with SCS for recurrent TCS, who experienced reduced pain but did not have any improvement in bowel or bladder function. 19 In contradistinction, our patient with recurrent TCS without radiographic tethering had complete resolution of symptoms and returned to normal genitourinary and sexual function.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…68 Our systematic review did reveal a patient treated with SCS for recurrent TCS, who experienced reduced pain but did not have any improvement in bowel or bladder function. 19 In contradistinction, our patient with recurrent TCS without radiographic tethering had complete resolution of symptoms and returned to normal genitourinary and sexual function.…”
Section: Discussionmentioning
confidence: 61%
“…17,18 Case reports have demonstrated pain reductions for pediatric patients undergoing SCS for recurrent tethered cord syndrome (TCS), lower-limb and pelvic pain due to widespread lymphangioma, and chronic visceral pain due to abdominal adhesions and mesenteric ischemia. [19][20][21] Other rare pediatric pain conditions for which SCS has been used include erythromelalgia, neuropathic pain with concomitant structural diseases such as macrodactyly, vascular malformations, and Klippel-Trenaunay-Weber syndrome with sciatic neuroma formation. [22][23][24][25][26] To the best of our knowledge, SCS use in the pediatric population has not been described in other pain syndromes.…”
mentioning
confidence: 99%
“…In addition, some patients refused to take surgical treatment, and their symptoms were further aggravated or new symptoms appeared followed by telephone or outpatient follow-up. [20] Therefore, early diagnosis and early surgical treatment will be possible to obtain a better prognosis for patients with symptomatic adult TCS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of spinal cord stimulation for the management of neuropathic pain is well established a literature review regarding its use in patients with pain secondary to tethered cord syndrome is limited. Our literature search highlighted two previous case reports describing its use in two adult patients Moens, et al [10] & Tyagi et al [11] Both of which reported a significant benefit in the management of pain for these patients. Moens reported its usage in a 37-year-old female patient with neuropathic pain following a history 14 years previously of untethering her spinal cord and excision of a sacral myelomeningocele with a single lead inserted at T12.…”
Section: Open Access Journal Of Neurology and Neurosurgerymentioning
confidence: 73%
“…Moens reported its usage in a 37-year-old female patient with neuropathic pain following a history 14 years previously of untethering her spinal cord and excision of a sacral myelomeningocele with a single lead inserted at T12. Tyagi et al [11] reported its usage in 19-year-old patient that had a cord untethering procedure for a lipomyelomeningocele at the age of 12 and then again at the age of 19. They inserted two leads at the level of T8.…”
Section: Open Access Journal Of Neurology and Neurosurgerymentioning
confidence: 99%